Reactive Oxygen Species-Related Ceftazidime Resistance Is Caused by the Pyruvate Cycle Perturbation and Reverted by Fe3 + in Edwardsiella tarda - Ye, Jinzhou; Su, Yubin; Peng, Xuanxian; Li, Hui (Frontiers in Microbiology, 2021)
Reactive oxygen species (ROS) are related to antibiotic resistance has been reported in bacteria. However, whether ROS contributes to ceftazidime resistance and plays a role in ceftazidime-mediated killing are absent. The present study showed lower ROS production in ceftazidime-resistant Edwardsiella tarda (LTB4-RCAZ) than LTB4-sensitive E. tarda (LTB4-S), two isogenic E. tarda LTB4 strains, which was related to bacterial viability in the presence of ceftazidime. Consistently, ROS promoter Fe3+ and inhibitor thiourea elevated and reduced the ceftazidime-mediated killing, respectively. Further investigation indicated that the reduction of ROS is related to inactivation of the pyruvate cycle, which provides sources for ROS biosynthesis, but not superoxide dismutase and catalase, which degrade ROS. Interestingly, Fe3+ promoted the pyruvate cycle, increased ROS biosynthesis and thereby promoted ceftazidime-mediated killing. The Fe3+-induced potentiation is generalizable to cephalosporins and clinically isolated multidrug-resistant pathogens. These results show that ROS plays a role in bacterial resistance and sensitivity to ceftazidime. More importantly, the present study reveals a previously unknown mechanism that Fe3+ elevates ROS production via promoting the pyruvate cycle.